Penerapan Metode Simple Multi Attribute Rating Technique Pada Pemberian Bonus Tahunan Karyawan - Sari Andriani; Allsela Meiriza (Maranatha University Press, 2021)
Employees are one of the most important aspects of a company. Quality employees will improve the quality of the company. To encourage employees to give their best to the company, companies can give bonuses to their employees. PT Budi Gema Gempita (BGG) is one of the companies that provides annual bonuses to its employees. In determining which employees will receive bonuses, PT Budi Gema Gempita (BGG) still uses paper to make an assessment. a decission support system is needed which can help Budi Gema Gempita (BGG), especially Human Resource Development (HRD) and division heads in the process of giving bonuses. The Simple Multi Attribute Rating Technique (SMART) method will be used because of its simplicity at responding to the needs of decision makers and how it responds. SMART is a multi-criteria decision method and a linear additive model to predict the value of each option. The use of SMART method is expected to provide the best recomendations for leaders to provide bonuses to employees